Thin Layer Chromatography Densitometric Determination of Soybean Isoflavones in Wild Soybean (Glycine soja) Seeds - Huang, Meng; Liu, Daicheng (Asian Journal of Chemistry, 2011)
A simple and selective method for qualitative and quantitative analysis of four soybean isoflavones in wild soybean seeds was validated. The isoflavones tested include daidzin, genistin, daidzein and genistein, which were identified by comparing with the standards and quantified simultaneously by thin layer chromatography densitometric method. Thin layer chromatography separation was performed on silica gel 60F254 [10 × 20 cm2] using dichloromethane:methanol:acetic acid (10:2:0.1,v/v) as the mobile phase for two b-glucosides (daidzin and genistin); chloroform:methanol:acetic acid (9:1:0.15,v/v) for two aglycones (daidzein and genistein). Densitometric evaluation of the spots was performed with a thin layer chromatography scanner in reflection/absorption mode at 260 nm. Average recoveries of daidzin, genistin, daidzein and genistein were 97.45, 98.32, 97.87 and 99.74 %, respectively; the total content of the four isoflavones was 42.471 (mg/g), which is the highest level in glycine species. The method elucidated above is appropriate for detection of isoflavones in wild soybean due to its specificity, accuracy and reproducibility.